2015
DOI: 10.4236/fns.2015.615144
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Six Microorganisms from Rotten <i> Dioscorea alata </i> (Water Yam), and Antimicrobial Sensitivity Test with Nine Plant Extracts

Abstract: Six microorganisms: four fungi-Aspergillus niger, Aspergillus flavus, Rhizopus stolonifera, Penicillium marneffei, two bacteria-Erwinia carotovora and Pseudomonas aeruginosa were isolated and identified from three rotten Dioscorea alata (water yam) varieties from two sites each in two local government areas of Benue State, Nigeria, in West Africa, between the months of May 2014 and May 2015. Pathogenicity test carried out using the microorganisms confirmed them to be the pathological agents of the rot. Antimic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“…Onuh et al, reported that aqueous extracts of the peel of Passiflora edulis showed strong inhibition of some fungi, especially Rhizopus stolonifer, Aspergillus niger and Penicillium marneffei. Peel extracts were inhibitory towards P. aeruginosa, which is not in agreement with our findings 21 .…”
Section: Discussioncontrasting
confidence: 86%
“…Onuh et al, reported that aqueous extracts of the peel of Passiflora edulis showed strong inhibition of some fungi, especially Rhizopus stolonifer, Aspergillus niger and Penicillium marneffei. Peel extracts were inhibitory towards P. aeruginosa, which is not in agreement with our findings 21 .…”
Section: Discussioncontrasting
confidence: 86%
“…The complete inhibition of the four bacteria (Erwinia carotovora, Pseudomonas aeruginosa, Serratia marcescens and Klebsiella oxytoca) by the synergistic plants extract (Ceiba pentandra, Jatropha tanjorensis, Azadarichta indica, Moringa Oleifera, Carica papaya, Mangifera indica, Daniella oliveri, Terminalia catapa and Passiflora edulis) has not yet been reported by other workers, using [8]; most probably because the concentration of the individual plants in the synergistic mixture was not sufficient to give complete inhibition; more so that inhibition increases with increase in concentration of the plant extract. All the fungi studied showed lower inhibition with synergistic extract compared with single extract and showed a gradual increase in inhibition with increase in concentration of the synergistic extract.…”
Section: Discussionmentioning
confidence: 98%
“…Our earlier studies as well as other researchers show that bacteria and fungi are responsible for the highest losses [5] [6] [7] [8]. Research has shown that these loss causing organisms exist in an associative growth with each organism causing its characteristic damage which is evident in tissue damage and coloration [7] [8].…”
mentioning
confidence: 99%
“…It can thus be said that appreciable growth reduction of the isolated fungi is dependent amongst other factors on the type of extract engaged as well as the concentration of the extracts. Onuh et al, (2015) reported that the higher the concentration, the more effective the plant extract on mycelial growth inhibition. The highly significant F value (P>0.0001) for plant part and fungi means that extract from any particular plant part will most likely exert significantly different antifungal effect on two different fungi.…”
Section: Discussionmentioning
confidence: 99%